IMPLEMENTASI METODE FINGER PAINTING DAN MAGIC PAINTING DALAM MENGEMBANGKAN KRETIVITAS ANAK DI TK FAMILY KANANTA - Nurwiriani, Riti; Abdussahid; Muslim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is based on the importance of fostering creativity in young children through exploratory and enjoyable activities. At Family Kananta Kindergarten, teachers strive to find learning methods that allow children freedom of expression while stimulating their fine motor skills, imagination, and symbolic thinking abilities. To address these needs, the finger painting and magic painting methods were implemented as tools for children to express their ideas and feelings through the touch of color and texture. The objective of this study is to factually describe the implementation process of these two methods and to identify their impact on children’s creative development. This is a qualitative descriptive study using a field study approach. Research data sources include teachers, students, and documents of children’s artwork at Family Kananta Kindergarten. Data collection techniques were conducted through direct observation of the activity process, in-depth interviews with teachers, and documentation of the children’s work. The research procedure included the stages of planning, implementation, observation, and reflection on learning outcomes. The data obtained were analyzed using data reduction techniques, data presentation, and inductive reasoning to draw conclusions. The research results indicate that the implementation of the finger painting and magic painting methods successfully fostered children’s creativity comprehensively. Children became more active, more confident in expressing themselves, capable of generating original visual ideas, and demonstrated significant improvements in fine motor coordination. Additionally, their self-confidence, symbolic and imaginative thinking skills, as well as collaborative attitudes and empathy, grew through shared activities. These methods have proven effective in creating a creative, enjoyable, and meaningful learning environment at Family Kananta Kindergarten.